The Role of Exercise-Induced Molecular Processes and Vitamin D in Improving Cardiorespiratory Fitness and Cardiac Rehabilitation in Patients With Heart Failure - Aleksova, Aneta; Janjusevic, Milijana; Gagno, Giulia; Pierri, Alessandro; Padoan, Laura; Fluca, Alessandra Lucia; Carriere, Cosimo; Beltrami, Antonio Paolo; Sinagra, Gianfranco (Frontiers in Physiology, 2022)
Heart failure (HF) still affects millions of people worldwide despite great advances in therapeutic approaches in the cardiovascular field. Remarkably, unlike pathological hypertrophy, exercise leads to beneficial cardiac hypertrophy characterized by normal or enhanced contractile function. Exercise-based cardiac rehabilitation improves cardiorespiratory fitness and, as a consequence, ameliorates the quality of life of patients with HF. Particularly, multiple studies demonstrated the improvement in left ventricular ejection fraction (LVEF) among patients with HF due to the various processes in the myocardium triggered by exercise. Exercise stimulates IGF-1/PI3K/Akt pathway activation involved in muscle growth in both the myocardium and skeletal muscle by regulating protein synthesis and catabolism. Also, physical activity stimulates the activation of the mitogen-activated protein kinase (MAPK) pathway which regulates cellular proliferation, differentiation and apoptosis. In addition, emerging data pointed out the anti-inflammatory effects of exercises as well. Therefore, it is of utmost importance for clinicians to accurately evaluate the patient’s condition by performing a cardiopulmonary exercise test and/or a six-minute walking test. Portable devices with the possibility to measure exercise capacity proved to be very useful in this setting as well. The aim of this review is to gather together the molecular processes triggered by the exercise and available therapies in HF settings that could ameliorate heart performance, with a special focus on strategies such as exercise-based cardiac rehabilitation.